Engineering fluid mechanics - Crowe, Clayton T.; Roberson, John A.; Elger, Don. (New York : John Wiley and Sons, 2000)
This book is about: Fluid properties; Fluid statics; Fluids in motion; Pressure variation in flowing fluids; Momentum principle; Dimensional analysis and similitude; ...
Keywords: Fluid mechanics; Fluid mechanics